The Turkish Foreign Ministry towards Lib - خضور عهد; معن ديوب (Latakia University Journal - Economic and Legal Sciences Series, 2025)
The international changes that occurred in the year 2011 greatly affected Turkish foreign policy, which was looking for influence in the region, and the Arab countries were the focus of attention of American foreign policy, especially those that witnessed crises such as the Libyan state, which Turkey saw as a very important country. By virtue of its richness in resources and oil wealth, as well as its important geographical location being close to Europe, Libya is therefore considered an important country for Turkey and therefore it set all its goals to intervene in it, and this is what happened through its support for parties at the expense of other parties, and the establishment of military bases where Turkey was trying to exploit the circumstances. International efforts to increase its influence in the North African region, especially in Libya, which is rich in oil and gas, and to restore the prestige of the Turkish state in the region.